Problems and Disadvantages of the Introduction of Modern Medicine in the Turkestan Governor-General - Jumanazarov, Khurshid Sirojiddinovich (International Journal on Integrated Education, 2023)
In this article researched problems of Turkestan governor generalship’s implementation of modern healthcare in Turkestan and mistakes by the government. The goals of government by the implementation of healthcare and studied The problems encountered by the peoples of the country in accepting the new system.